2008
DOI: 10.1007/s11069-008-9320-9
|View full text |Cite
|
Sign up to set email alerts
|

Sea surface temperature trends in Kuwait Bay, Arabian Gulf

Abstract: The waters of Kuwait Bay, northern Arabian Gulf, are well mixed by macrotidal, semi-diurnal tides. Sea surface temperature (SST) is thus a good proxy of water mass temperature in the bay. The factors governing SST have been conveniently subdivided into global, regional and local drivers. This paper provides a study on long-term drivers of temperature change in the northern Arabian Gulf: that is, factors that influence decadal changes. AVHRR (NOAA) satellite data of Kuwait Bay, collected between 1985 and 2002, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 15 publications
5
35
0
Order By: Relevance
“…Of 39 stations reported, almost all showed significant warming together with a mean warming trend of 0.58C/decade in the southern North Sea. Similarly dramatic warming trends have been found in the surface waters of Tokyo Bay, Japan (Yanagi, 2008); South Korea (Jung, 2008); the inner Arabian Gulf (Al Rashidi et al, 2009); the southern Bay of Biscay (Goikoetxea et al, 2009;Koutsikopoulis et al, 1998); Woods Hole, Massachusetts, United States (Nixon et al, 2004); Chesapeake Bay, USA (Preston, 2004); the Wadden Sea, Netherlands (van Aken, 2008), the northern North Sea (Wiltshire and Manly, 2004); and east coast USA estuaries (Jones, Lima, and Wethey, 2010). Inland waters and large lakes appear to be warming at similar or more rapid rates than coastal waters (Austin and Colman, 2008;Schneider and Hook, 2010).…”
Section: Global Comparison Of Sst Trends With Other Coastal Sitesmentioning
confidence: 52%
See 1 more Smart Citation
“…Of 39 stations reported, almost all showed significant warming together with a mean warming trend of 0.58C/decade in the southern North Sea. Similarly dramatic warming trends have been found in the surface waters of Tokyo Bay, Japan (Yanagi, 2008); South Korea (Jung, 2008); the inner Arabian Gulf (Al Rashidi et al, 2009); the southern Bay of Biscay (Goikoetxea et al, 2009;Koutsikopoulis et al, 1998); Woods Hole, Massachusetts, United States (Nixon et al, 2004); Chesapeake Bay, USA (Preston, 2004); the Wadden Sea, Netherlands (van Aken, 2008), the northern North Sea (Wiltshire and Manly, 2004); and east coast USA estuaries (Jones, Lima, and Wethey, 2010). Inland waters and large lakes appear to be warming at similar or more rapid rates than coastal waters (Austin and Colman, 2008;Schneider and Hook, 2010).…”
Section: Global Comparison Of Sst Trends With Other Coastal Sitesmentioning
confidence: 52%
“…Thus, local effects of urbanization are expected to increase. Al Rashidi et al (2009) distinguish between local, regional, and global drivers of SST in the Arabian Gulf and demonstrated that local and regional contributions to temperature trends have dominated over the global trend in the last 20 years: The local drivers were linked to human activities related to urbanisation of the coastal zone (Gonzalez et al, 2005;Oke, 2011). The global trend in SST has been þ0.28C/decade since 1990 (IPCC, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic activities have significant impacts on marine environment by increasing seawater temperature. Reference [30] found that the seawater temperature in Kuwait Bay has increased by an average 0.6 º C per decade, about three times higher than the global average rate reported by the Intergovernmental Panel on Climate Change (IPCC). Moreover, he concluded that desalination and power plants contribute by 13% of decadal increasing in the seawater temperature in Kuwait Bay.…”
Section: A Summary Statistics Of Water Quality Parametersmentioning
confidence: 91%
“…The environmental conditions found in some marine ecosystems may change to become physiologically incompatible with the biology of local species, forcing these species to either relocate or face local extinction. For example, most coral reef fishes found in the Red Sea and Arabian peninsula are absent from reefs in the Arabian gulf where temperatures can reach >35°C during summer months (Al-Rashidi, El-Gamily, Amos, & Rakha, 2009; Burt et al, 2011). The absence of species in the gulf despite suitable habitat and food suggests that these species have an upper limit for thermal adaptation (Al-Rashidi et al, 2009; Burt et al, 2011).…”
Section: Physiological Drivers Of Animal Behaviour Across Biomes and mentioning
confidence: 99%
“…For example, most coral reef fishes found in the Red Sea and Arabian peninsula are absent from reefs in the Arabian gulf where temperatures can reach >35°C during summer months (Al-Rashidi, El-Gamily, Amos, & Rakha, 2009; Burt et al, 2011). The absence of species in the gulf despite suitable habitat and food suggests that these species have an upper limit for thermal adaptation (Al-Rashidi et al, 2009; Burt et al, 2011). Similarly, recent work on equatorial fish populations has revealed reduced capacities to tolerate the 3 ° C temperature increase expected by 2100 (Rummer et al, 2014), while populations at higher latitudes appear better able to tolerate comparable temperature rises (Gardiner, Munday, & Nilsson, 2010; McLeod et al, 2015; Takahashi, McCormick, Munday, & Jones, 2012).…”
Section: Physiological Drivers Of Animal Behaviour Across Biomes and mentioning
confidence: 99%